Impact Of Brand Reengineering Strategies On Consumers Mindset (Journal of Pharmaceutical Negative Results, 2021)
This research paper investigates the impact of brand reengineering strategies on consumer perceptions and behaviours. Through a quantitative study, data were collected from a sample of 286 respondents to explore the influence of brand revitalization initiatives on consumer actions, decision-making processes, and perceptions of brands. Likert-scale statements were utilized to measure respondents' agreement with various statements related to brand reengineering and its effects on their perceptions and behaviours. The findings reveal that brand revitalization efforts significantly influence consumer attitudes, purchase decisions, advocacy behaviour, and perceptions of brand quality, relevance, and innovation. The study highlights the strategic importance of brand reengineering in enhancing brand competitiveness and fostering positive consumer-brand relationships in dynamic market environments.